Nurse’s Practices toward Nursing Intervention of Diagnostic Procedures at Neuro Surgical Hospitals in Baghdad City (Indian Journal of Forensic Medicine & Toxicology, 2020)
The study aims to evaluate nurses’ practices toward nursing intervention of diagnostic procedures at NeuroSurgical Hospitals, and to find-out the relationship between Nurses’ practices with their Socio-demographiccharacteristic of age, gender, and education level. A quantitative research approach has been used for thisstudy design starting from December 7th, 2017 to September 2nd, 2019. A purposive sample was adoptedincluding (50) male and female nurses as participants. They were working at Neuro surgical Hospitals.The study Instrument was composed of two Parts: The First Part is concerned with the socio-demographiccharacteristics, and the second Part includes Nurses’ Practices. Content validity of the instrument wasestablished through a penal of (11) experts. Results have been analyzed through the use of SPSS “StatisticalPackage for Social Sciences” model 24.0 by using descriptive and inferential statistical methods. Findings ofthe present study revealed that most of the samples were within the age of (35-44) years who were accounted(34%). The age group of (25-34 years) represent (32%). 24 percent of the study sample were (45-54) yearsold, and only five nurses were within the age group of (18-24) years old.
Keywords: Nurses, practice, diagnostic procedures, neurosurgical.